Angular ellipticity correlations in a composite alignment model for elliptical and spiral galaxies and inference from weak lensing - Tugendhat, Tim; Schäfer, Björn Malte (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. We investigate a physical, composite alignment model for both spiral and elliptical galaxies and its impact on cosmological parameter estimation from